2013
DOI: 10.1016/j.jcma.2013.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of liver trauma and relative risk factors for mortality: A population-based study

Abstract: The overall incidence rate of liver trauma was higher in the younger age group and in rural residents. A higher risk of mortality was found in the age > 64 years group, pedestrians hit in motor-vehicle accidents, renal failure or liver cirrhosis, with head or chest, or other abdominal injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 27 publications
5
18
0
1
Order By: Relevance
“…The most affected population is in the age group 21-30 (21 patients). Similar results were found in study done by chienn lc et al 6 The higher incidence of liver injuries in younger population corresponds to their proneness to get involved in road traffic accidents.…”
Section: Resultssupporting
confidence: 91%
“…The most affected population is in the age group 21-30 (21 patients). Similar results were found in study done by chienn lc et al 6 The higher incidence of liver injuries in younger population corresponds to their proneness to get involved in road traffic accidents.…”
Section: Resultssupporting
confidence: 91%
“…The mean age of patients was 34.85±9.75 years. 17 The findings were similar to present study where most patients were males as well as similar mean age of patients was reported.…”
Section: Discussionsupporting
confidence: 92%
“…Traffic accidents account for the majority of liver injuries [3]. The incidence of traumatic liver injury in total population is 2.95-13.9/100.000 [4,5]. Thirteen to 16% of polytrauma patients have liver injuries [6].…”
Section: Introductionmentioning
confidence: 99%